Komparasi Model Problem Based Learning Dan Discovery Learning Terhadap Hasil Belajar Ditinjau Dari Kemampuan Awal - Silvia Shinta; Sri Fatmawati; Muhammad Nasir (Kappa Journal, 2020)
This study aims to determine: (1) Is there a difference in influence between the Problem based learning  and Discovery learning models on student learning outcomes (2) Are there differences in influence between students with high initial ability and low initial ability towards learning outcomes (3) Are there interactions between the Problem based learning  and Discovery learning learning models with initial abilities towards learning outcomes? This study aims to examine the comparative learning model of problem based learning and discovery learning towards learning outcomes in terms of ability early.This study used an experimental method with the only group posttest design and factorial design with population of the whole MIPA class XI and  sampling using purposive sampling, the selected sample was XI-MIPA 1 and XI MIPA 4. The instrument used was an initial ability test and a learning achievement test. The results of this study indicate that: (1) There is a significant difference in influence between problem based learning and discovery learning models on learning outcomes with a value of sig * 0,000 which means <Î± where Î± = 0.05 (2) There is a significant difference in influence between high initial ability and low initial ability of learning outcomes with a value of sig * 0.023 which means <Î± where Î± = 0.05 (3) There is no interaction between the learning model of problem based learning and discovery learning with the initial ability to student learning outcomes with a value of sig * 0.368 which means> Î± where Î± = 0.05.  DOI: 10.29408/kpj.v4i1.1718